A Study of Synchronous and Asynchronous Approaches: Online Arabic Learning During The Covid-19 Pandemic - Khoirin Nikmah; Nahdliyyatul Azimah (Prodi Bahasa Arab dan Lembaga Bahasa Institut Pesantren KH Abdul Chalim Mojokerto, 2020)
Purpose:This study focuses on an online Arabic learning through synchronous and asynchronous approaches. Meanwhile, the aims of this study are; 1) describing implementation of synchronous and asynchronous online Arabic learning in higher education, 2) investigating its advantages and disadvantages, 3) offering solutions in learning Arabic through e-learning. Design/methodology/approach:This is a descriptive qualitative research that applies an observation method, interview, and documentation to collect the data. Afterwards, identity method is used to investigate the data. Then, triangulation is applied for validity check Findings/result:The result shows that synchronous e-learning is the most widely applied in learning Arabic for IPIREL UMY (75 %) and IPIEF UMY (62%). On the contrary, Arabic learning (IBA) at UINSA tends to apply asynchronous e-learning (75%). Originality/value:It is important for lecturer to prepare the best method and media for distance learning. By understanding what students need, lecturer may determine how important for students to learn Arabic through synchronous or asynchronous approach. Paper type:Research paper